2017
DOI: 10.1016/j.ijsu.2017.01.115
|View full text |Cite
|
Sign up to set email alerts
|

The Charlson age comorbidity index predicts prognosis in patients with resected pancreatic cancer

Abstract: The CACI was a significant independent predictor of prognosis and compliance for postoperative adjuvant chemotherapy in the resected pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…Besides this, age and differentiation grade were further incorporated into the novel model. Asano et al 27 had reported the role of age in the survival of resected PC patients. Surgery was considered as a giant damage to patients’ physical functions and immune system, which may lead to serious comorbidities and mortalities.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, age and differentiation grade were further incorporated into the novel model. Asano et al 27 had reported the role of age in the survival of resected PC patients. Surgery was considered as a giant damage to patients’ physical functions and immune system, which may lead to serious comorbidities and mortalities.…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative Charlson age-comorbidity index (CACI) was calculated from available data as a measure of frailty and patients were dichotomized using a threshold of 4 points based on recent literature. 1618 Pre- and postoperative carbohydrate antigen (CA) 19–9 values were obtained, when available. CA 19–9 values acquired at time of jaundice (total bilirubin > 5mg/dL) or later than 2 months postoperatively were excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A CACI score > 4 was predictive for increased duration of hospitalisation and risk of postoperative complications, and a threefold higher risk of death within the first year was found in patients with a CACI score ≥ 6. In 379 patients who underwent resection for PC, the CACI score was an independent prognostic factor for short‐ and long‐term outcome and patients with CACI < 4 had better compliance for postoperative adjuvant chemotherapy than patients with CACI ≥ 4 (Asano et al, ). In 194 patients with locally advanced PDAC treated with intraoperative radiotherapy combined with chemotherapy, a CACI of ≤ 3 and treatment with chemotherapy predicted improved OS (Cai et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Precautions exist when using scoring to control for comorbidities including missing weighting for particular comorbidities as well as uncertainty concerning comprehensiveness of the conditions (Elixhauser, Steiner, Harris, & Coffey, ). Higher CACI is associated with poorer OS in resected PC patients and patients with unresectable locally advanced PC treated with intraoperative radiotherapy (Asano et al, ; Cai et al, ; Dias‐Santos, Ferrone, Zheng, Lillemoe, & Fernández‐Del, ). There are no studies addressing specifically the prognostic value of CACI and its interplay with other risk factors in a real‐world cohort of PC patients undergoing adjuvant or palliative chemotherapy.…”
Section: Introductionmentioning
confidence: 99%